2017
DOI: 10.1177/0016986217722614
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Spatial Ability of Undergraduate Students: Association With Gender, STEM Majors, and Gifted Program Membership

Abstract: Spatial ability has been valued as a talent domain and as an assessment form that reduces cultural, linguistic, and socioeconomic status biases, yet little is known of the spatial ability of students in gifted programs compared with those in general education. Spatial ability is considered an important indicator of potential talent in the domains of science, technology, engineering, and mathematics (STEM). This study explored undergraduate students’ spatial ability, focusing on mental rotation, by investigatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 59 publications
2
26
0
2
Order By: Relevance
“…The interpretation and comprehension of these forms of visual-spatial representations should theoretically place demands on the individual’s spatial processing abilities (Hegarty, 2014; Stieff and Uttal, 2015; Newcombe, 2016; Verdine et al, 2017). Consistent with the assumption, numerous studies on adults show that measures of spatial ability such as mental rotation and spatial visualization are predictive of concurrent and future accomplishment in science (Hegarty and Sims, 1994 spatial visualization; Paper Folding Test; speeded rotation, spatial orientation; Kell et al, 2013 spatial visualization; Kozhevnikov et al, 2007 spatial visualization; Shea et al, 2001; Wai et al, 2009 spatial visualization; Webb et al, 2007 mental rotation; Yoon and Mann, 2017 mental rotation). Furthermore, a few intervention studies provide evidence that training spatial ability can improve science learning in university students (Sorby, 2009; Miller and Halpern, 2013).…”
Section: Introductionmentioning
confidence: 70%
“…The interpretation and comprehension of these forms of visual-spatial representations should theoretically place demands on the individual’s spatial processing abilities (Hegarty, 2014; Stieff and Uttal, 2015; Newcombe, 2016; Verdine et al, 2017). Consistent with the assumption, numerous studies on adults show that measures of spatial ability such as mental rotation and spatial visualization are predictive of concurrent and future accomplishment in science (Hegarty and Sims, 1994 spatial visualization; Paper Folding Test; speeded rotation, spatial orientation; Kell et al, 2013 spatial visualization; Kozhevnikov et al, 2007 spatial visualization; Shea et al, 2001; Wai et al, 2009 spatial visualization; Webb et al, 2007 mental rotation; Yoon and Mann, 2017 mental rotation). Furthermore, a few intervention studies provide evidence that training spatial ability can improve science learning in university students (Sorby, 2009; Miller and Halpern, 2013).…”
Section: Introductionmentioning
confidence: 70%
“…The revised test is named as revised PSVT:R. Since then, the revised PSVT:R has been used in several studies to investigate the psychometric properties of the test questions through Item Response Theory (IRT) Models . They were also used to explore the association of the spatial ability of undergraduate students with gender, STEM majors and gifted program membership (Yoon and Mann, 2017).…”
Section: Psvt: R and Revised Psvt:rmentioning
confidence: 99%
“…Robert and Chevrier (2003) reported similar numbers of correct answers among men and women when no time limit was established in mental rotation test, although men answered the items more quickly than women. Whilst some studies showed that such gender differences are more pronounced when the time to do the test is limited in mental rotation test (Voyer and Saunders, 2004;Peters, 2005;Voyer, 2011;Maeda and Yoon, 2016), others designed to assess mental rotation aptitudes reported no statistically significant differences between the sexes in completion time (Yoon and Mann, 2017). A third group observed males to score higher on visual tests irrespective of the existence of time limitations in mental rotation test (Delgado and Prieto, 1996;Geiser et al, 2006) or other figure analogy test (Blum et al, 2015).…”
Section: Gender Differences In Visuospatial Ability: Performance Factorsmentioning
confidence: 99%